Comparative study of biodegradation of municipal solid waste in simulated aerobic and anaerobic bioreactors landfills - Rendra, Septa (University of Ottawa (Canada), 2007)
The biodegradation of municipal solid waste (MSW) was investigated in simulated bioreactor landfills under aerobic and anaerobic conditions. The bioreactors were operated to determine the amount of leachate recirculation and municipal wastewater sludge addition to optimize waste degradation. The leachate generated was recycled over 47 and 63 weeks for aerobic and anaerobic bioreactors, respectively. Leachate samples were collected on a weekly basis and analyzed for pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total Kjeldahl nitrogen (TKN), ammonia nitrogen (NH3-N), total phosporus, and metals. The temperature of the MSW in the bioreactors was measured on a daily basis. In addition, the generation of biogas was monitored in the anaerobic bioreactors during the operating period. The leachate generated was recirculated at the rates of 285 to 855 mL/kg of MSW.d (5 to 15 L/wk) and sludge was added at the rates of 28.5 to 85.5 mL/kg of MSW.d (0.5 to 1.5 L/wk). Within 27 and 39 weeks enhanced MSW degradation in the aerobic and anaerobic bioreactors were observed at a leachate recirculation rate of 855 mL/kg of MSW.d and sludge addition rate of 85.5 mL/kg of MSW.d. During this period, the COD concentration in the leachate dropped from 38,000 mg/L for aerobic and 47,000 mg/L for anaerobic to approximately 1000 mg/L. This is an indication that the aerobic biodegradation is 1.5-fold faster compared to the biodegradation under anaerobic operation. A reduction in the leachate recirculation and sludge addition rate to 285 and 28.5 mL/kg of MSW.d respectively, increased the waste stabilization period up to 45 and 63 weeks for aerobic and anaerobic bioreactors, respectively. The statistical empirical models based on two levels factorial design were used to describe the effects of leachate recirculation, sludge addition and their combination on biodegradation of the waste. For both aerobic and anaerobic bioreactors the values of estimate parameter beta1 were higher compared to beta2 and beta12. This indicated that the effect of leachate recirculation was much stronger compared to the effect of sludge addition and their combination on biodegradation of the waste. A statistic procedure, F-test and ANOVA-test were used to determine whether or not there is a significant difference between the aerobic and anaerobic biodegradation. The result of the paired F-test show that F calculation was 270.85 and F critical was 160 at a 95% confidence level. This confirms that there was a significant difference between the aerobic and anaerobic biodegradation. In addition, the ANOVA test show that effect of air flow addition on the MSW biodegradation was very significant. The results of these tests indicated that the addition of air affected positively the biological activities and consequently enhanced the MSW biodegradation process. A fuzzy logic model, describing the dynamics of the biodegradation and stabilization process during the experiment, was developed to simulate the effect of leachate recirculation and sludge addition on MSW biodegradation in landfills. The model was based on the COD concentration of the leachate, temperature of the MSW in the bioreactors, and biogas production from anaerobic bioreactors. Subsequently, the model was evaluated by comparing the simulation with the experimental results. The model shows that the higher rate of leachate recirculation and sludge addition, the faster biodegradation of MSW. In addition, the model could be used to predict the rate of MSW biodegradation under various operating conditions.
Keywords: Engineering, Civil.; Engineering, Sanitary and Municipal.; Environmental Sciences.